2011
DOI: 10.17925/ohr.2011.07.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Acute Venous Thrombosis

Abstract: Venous thromboembolism (VTE) includes both deep vein thrombosis (DVT) and pulmonary embolism (PE). VTE occurs worldwide, and in all age groups and socioeconomic populations in North America and western Europe.1,2 In a recent study by Heit et al., the estimated total annual cases of VTE occurring in the US exceeded 900,000, of which more than 250,000 were fatal. 3 Despite progress in medicine and biology, no changes in the incidence of VTE were noted during the 25-year cohort study. InflammationInflammation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…In mouse models, elevated galectin-3 is correlated with thrombus size, and in human patients it correlated with acute VT. 9 The partial attenuation of the association between galectin-3 and VTE by other inflammatory and cardiac biomarkers suggests that galectin-3 level may also reflect the role of inflammation in VTE pathogenesis. 6,8 This attenuation may be the result of the other biomarkers being mediators of the galectin-3 association with VTE or reflect similar pathways between these biomarkers in VTE pathogenesis. Galectin-3 has been reported to interact with gal3bp at the thrombus-vein wall interface, and may contribute to thrombosis through proinflammatory, interleukin-6-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mouse models, elevated galectin-3 is correlated with thrombus size, and in human patients it correlated with acute VT. 9 The partial attenuation of the association between galectin-3 and VTE by other inflammatory and cardiac biomarkers suggests that galectin-3 level may also reflect the role of inflammation in VTE pathogenesis. 6,8 This attenuation may be the result of the other biomarkers being mediators of the galectin-3 association with VTE or reflect similar pathways between these biomarkers in VTE pathogenesis. Galectin-3 has been reported to interact with gal3bp at the thrombus-vein wall interface, and may contribute to thrombosis through proinflammatory, interleukin-6-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thromboembolism (VTE), presenting as deep venous thrombosis (DVT) and/or pulmonary embolism (PE), is a major public health problem with a multifactorial etiology . Risk of VTE is increased in patients with inflammatory diseases or with elevated levels of inflammation markers, such as C‐reactive protein and interleukin‐6 . Among inflammatory pathways, galectin‐3–binding protein (gal3bp) and its receptor/ligand, galectin‐3, are secreted proteins that can interact with each other to promote cell‐to‐cell adhesion and initiate pathologic, proinflammatory signaling cascades .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Cell-to-cell adhesion plays a major role in thrombogenesis, both at the thrombus-vein wall interface and within the thrombus itself. 29,30 The adhesive properties of gal3 multimers may contribute to gal3's apparent prothrombotic function. We suspect that the increase in gal3 protein observed during VT in PLTs may be caused by in situ translation of preexisting gal3 mRNA, because PLTs, although lacking in nuclei, have been shown to possess translational machinery.…”
Section: Gal3bp and Gal3 Locationmentioning
confidence: 99%
“…Several studies examined the endothelial damage and dysfunction in DVT. A literature review indicated that, in patients in the acute phase of VTE, endothelial cells produced IL-6, platelet-activating factor, and other substances that affect the inflammatory response and involve the formation of thrombi [ 26 ]. Persistently increased levels of inflammatory factors, such as tumor necrosis factor alpha (TNF-α), IL-6, and CXCL-8, accompanied by certain markers of endothelial damage, such as tissue plasminogen activator (tPA), plasminogen activator inhibitor 1 (PAI-1), and vWF, were detected in patients with a history of idiopathic DVT.…”
Section: Discussionmentioning
confidence: 99%